(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
he article “Raising Ecological Awareness in the Younger Generation – An Important Educational Direction” explores the significance of ecological education in guiding the younger generation toward environmental protection. It emphasizes that environmental education not only imparts scientific knowledge but also fosters a sense of responsibility toward nature